Creative Space Foundation Metaverse - Tasya Monica; Widhea Ayu Santika; Eilen Monika; Iges Triasnita Miranda; Adi Setiawan (CV. Media Digital Publikasi Indonesia, 2024)
Creative spaces have become important places that encourage innovation, collaboration, and imagination in various fields. This study investigates the complex dynamics of creative spaces by studying physical, social, and psychological aspects. We do this from the perspective of different disciplines and designs and see how special characteristics and creative processes interact with each other. We investigate the influence of spatial confirmation, atmosphere, and accessibility on individual creativity and productivity in this setting using mixed methods, including qualitative case studies and quantitative analysis. Our results show that design components such as layout flexibility, natural lighting, and aesthetic appeal influence how people think and interact with others. All this forms a broad creative experience. In addition, this research investigates how organizational culture, leaders and community dynamics play a role in building and maintaining creative ecosystems in these places. By explaining the complex relationship between the physical environment and human behaviour our research offers insights for practitioners, policy makers, and educators who want to create better creative spaces for collaboration and innovation. Using the Visualization of Similarities (Vos Viewers) tool, this research uses qualitative and bibliometric techniques. Using Vos Viewers you can search 992 articles by entering keywords such as; creative space; digital space; customer experience; and metaverse reduction. The results of the analysis show scientific mapping and potential for future research regarding creative spaces as a new marketing world. These results can be used as recommendation variables for researchers conducting further research.